The impact of slope and rainfall on the contaminant transport from mountainous groundwater to the lowland surface water - Xu, Xiaojun; Zhu, Ming; Zhou, Ling; Ma, Mingxia; Heng, Jingmei; Lu, Li; Qu, Weiyi; Xu, Zhongyuan (Frontiers in Environmental Science, 2024)
The surface water and groundwater in the mountainous area are vulnerable to contamination from the mining and transportation construction in Sichuan Province, China. Pollutants produced by anthropogenic activities transport within the groundwater from mountains to rivers on the plain, transferring contamination to the surface water. This study investigates the process of groundwater flow and contaminant transport from mountains to the lowlands based on synthetic numerical models. Two key factors are considered: precipitation and the slope of the mountain. Based on the real situation in Sichuan Province, four rainfall recharge rates are defined as 600, 800, 1,000, and 1,200 mm/yr, and five slope angles are considered: 20°, 25°, 30°, 35°, and 40°. The simulation results reveal that the groundwater level and solute transport are strongly influenced by the precipitation amounts and slope angles. The mountains with lower slopes maintain a relatively higher groundwater level under steady-state rainfall conditions; for example, groundwater levels decrease from 340 m to 300 m as slope angles increase at a 1,200 mm/yr precipitation level. Contaminant transport from the source in the mountain to the surface river is faster with increasing precipitations and decreasing slope angles. The model with 20° slope angle and 1,200 mm/yr precipitation exhibits the fastest solute migration, with the contaminant arrival time of 65 years. Furthermore, the models with 35° and 40° slope angles at a 600 mm/yr precipitation level show the slow transport speed with the contaminant arrival time of more than 75 years. In addition, higher precipitation may lead to more contaminant transport to the river. The analysis and findings of this study offer valuable insights into groundwater protection at the boundaries of mountains and plains.